Perbedaan Efektivitas Obat Kumur yang Mengandung Chlorhexidine dan Essential Oils Terhadap Penurunan Tingkat Halitosis - Arum Dyah Pangesti; Desak Nym Ari Susanti; Sari Kusumadewi (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Halitosis is a malodor comes from the oral cavity and currently it becomes a serious problem that can cause low self-esteem to a person. The main cause of halitosis is the release of Volatile Sulfur Compounds (VSCs) produced by anaerobic bacterial activity in the oral cavity. One way to solve halitosis problem is by using mouthwash. Available mouthwashes in market contain chlorhexidine or essential oil. Chlorhexidine is a broad-spectrum antimicrobial drug. It roles as an antiseptic agent, an effective bactericidal agent against all kinds of microbe, including bacteria, yeast, and virus. An essential oils mouthwash has an antimicrobial effect and prevents bacterial aggregation. Its mechanism is through bacterial cell destruction, bacterial enzyme inhibition and endotoxin extraction from Gram negative bacteria that can cause halitosis. Experimental method is used in this study. It consists of 32 subjects divided into 2 group whom passed the inclusion criteria. Group 1 rinsed using chlorhexidine mouthwash and group 2 rinsed using essential oils mouthwash. The measurement was done before intervention, first 20 minutes, 40 minutes and 60 minutes. Datas were analyzed using Shapiro Wilk for normality test and nonparametric MannWhitney for statistical hypothesis test. There Was a significant different between chlorhexidine and essential oils mouthwashes in reducing halitosis level. Chlorhexidine is more effective in reducing halitosis when compared to essential oils.